Medium-term impact of COVID-19 on pulmonary function, functional capacity and quality of life. Issue 3 (16th September 2021) - Anastasio, Fabio; Barbuto, Sarah; Scarnecchia, Elisa; Cosma, Paolo; Fugagnoli, Alessandro; Rossi, Giulio; Parravicini, Mirco; Parravicini, Pierpaolo
Background: Coronavirus disease 2019 (COVID-19) has spread worldwide, having a dramatic impact on healthcare systems. The aim of this study is to evaluate mid-term clinical impact of COVID-19 on respiratory function. Methods: 379 patients were evaluated 4 months after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnosis. Patients were divided in two groups based on the presence of pneumonia during COVID-19. Clinical conditions, quality of life, symptomatology, 6-min walk test, pulmonary function test with spirometry and diffusing capacity of the lung for carbon monoxide were analysed. Data were compared to clinical evolution during COVID-19 (development of acute respiratory distress syndrome, need of invasive mechanical ventilation, partial oxygen saturation ( S pO2 )/inspiratory oxygen fraction ( F IO2 ) ratio and pneumonia severity index (PSI)). Results: After a median 135 days, 260 (68.6%) out of 379 patients referred at least one symptom. Patients who developed pneumonia during COVID-19 showed lower S pO2 at rest (p<0.001), S pO2 during 6-min walk test (p<0.001), total lung capacity (p<0.001), airway occlusion pressure after 0.1 s ( P 0.1 ) (p=0.02), P 0.1 /maximal inspiratory pressure ratio (p=0.005) and higher Borg category-ratio scale (p=0.006) and modified Medical Research Council breathlessness scale (p=0.003), compared to patients without pneumonia. S pO2 / F IO2 ratio and PSI during SARS-CoV-2 pneumonia were directly associated with mid-term alteration of S pO2 at rest (p<0.001) and during 6-min walk test (p<0.001), residual volume (p<0.001), total lung capacity (p<0.001 and p=0.003, respectively) and forced vital capacity (p=0.004 and p=0.03, respectively). Conclusion: Lung damage during COVID-19 correlates to the reduction of pulmonary function 4 months after acute infection. COVID-19 severe lung involvement can reduce respiratory performance in the medium- to long-term. Respiratory rehabilitation is recommended in COVID-19 survivors showing severe clinical and radiological signs of disease. https://bit.ly/3jCxN0s